Reducing Stereotypies for a Student With Deafblindness. (July 2021) - Singer, Isaac; Ivy, Sarah E.; Myers, Sasha
Introduction: Little is known about the effects of specific behavioral strategies to reduce stereotypy and self-injury for learners with sensory impairments and additional disabilities.Method: A single-subject, multi-treatment withdrawal design was used to test the isolated and combined effects of physical prompting to engage in object manipulation of preferred items, contingent reinforcement, and response blocking on target hand-related stereotypy and object manipulation for one 9-year-old boy with deafblindness and additional disabilities.Results: A functional relation was observed to show that hand-related stereotypy decreased due to prompting and reinforcement of object manipulation. Adding response blocking had inconsistent positive effects on stereotypy, and a functional relation was not observed. Prompting alone did not appear to increase object manipulation until contingent reinforcement was added, and response blocking did not appear to have an additive effect to increase object manipulation.Discussion: Results contradict findings of the replicated study and indicate need for further research, including research carried out in natural environments.Implications for Practitioners: Practitioners can use this research to justify the application of differential reinforcement of incompatible behavior using functional activities that result in meaningful reinforcement for students.